Islamic Personality Education Program for Teachers of General Subjects in High Schools - Imas Kania Rahman; Abdul Hadad (al-Afkar, Journal For Islamic Studies, 2025)
One of the spearheads of educational success is a teacher, because teachers not only teach more knowledge than that in Islamic teachings, teachers are also role models for their students, Imam Al-Ghazali said that a teacher must perfect his mind and morals (personality) and Ibnu Sahnun explained that the importance of personality that a teacher must have. Therefore, teachers must have a good personality as educators, in the learning and teaching process or in the surrounding environment. In order to achieve the expected education, of course the teacher's personality occupies an important position, especially students at high school level must have a teacher figure who can have a good influence on their personality. Therefore, there is a need for a personality education program for teachers. Researchers developed an Islamic personality education program for general subject teachers in high schools. Therefore, researchers chose the Research and Development method, the ADDIE development model. Researchers chose the ADDIE development model as the Research and Development method, the analysis phase of which is carried out by analyzing field and program needs. The design stage refers to the basics of the Islamic religion in general which include aqidah, sharia and morals. In the development phase, expert validation of the initial program was carried out involving curriculum experts, religious experts, linguists and educational practitioners, and a second program was produced. At the implementation stage, it is given to high school principals, high school curriculum coconuts, to high school teachers and to lecturers who guide curriculum analysis. In the evaluation stage, improvements are made based on the users of the second program until it becomes the final program.